Microencapsulation of Fe2+ in Spray-Dried Lactose for Improved Bioavailability - Nan Li; Xu Li; Ping Yang; Hongbin Liu; Lingyu Kong; Xiaomeng Yu (Bioinorganic Chemistry and Applications)
The development of spray drying technology has been widely used for drying and preservation of food products. Though infant milk powder iron fortification is necessary for infants and children, iron fortification is accompanied by some limitations that reduce its quality and oxidation of Fe2+ into Fe3+, causing sensory problems and even a decrease in iron absorption, which does not meet the normal requirements of infant and child body development. To overcome this adverse effect and to improve the bioavailability of iron, a spray drying method was used to simulate the milk powder production process by codrying a mixture of ascorbic acid and ferrous sulfate, where ascorbic acid was uniformly coated on the outer layer of ferrous sulfate. It was demonstrated that ascorbic acid had a very obvious inhibitory effect on the oxidation of ferrous iron and could maintain the stability of ferrous iron in solid and solution for a long time, thus improving the bioavailability of iron.